USE OF GAME TYPES IN THE DEVELOPMENT OF GENDER CULTURE OF ADOLESCENT STUDENTS (American Journal of Research in Humanities and Social Sciences, 2023)
This article is devoted to the issues of using games and their types in the development of gender culture of adolescent students. It is noted that games are classified according to their content, time of holding, place, level of management, number of participants and composition.